Enhancing Literacy Achievement Among Junior High School Students in West Sumbawa Regency through the Digital Microsite Go Jamu Sumbar - Minten Ayu Larassati; Fitria Yuliana; Hari Asgar (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study aims to examine the strategies and stages involved in integrating the Go Jamu Sumbar digital microsite into the learning process and to evaluate its effectiveness in enhancing literacy development among junior high school students in West Sumbawa Regency (KSB) across cognitive, affective, and psychomotor domains. The research engaged key stakeholders, including representatives from the Ministry of Education and Culture, school principals, teachers, and students from ten pilot junior high schools. Data were collected through observations, structured tests, in-depth interviews, and Focus Group Discussions (FGDs). Employing a qualitative research design grounded in the post-positivist paradigm, the study was conducted in natural settings using an inductive approach that emphasizes meaning rather than generalization, with participants selected through purposive sampling. The findings reveal that the main strategies for implementation include socialization, teacher training, integration of digital technology into daily school routines and curricula, innovation in creative and physical literacy activities, utilization of digital infrastructure, enhancement of teachers’ digital competencies, classroom mentoring, strengthening of students’ interest and motivation, as well as institutional support and government policies through regional literacy initiatives. In conclusion, the Go Jamu Sumbar digital microsite has been effectively integrated into ten pilot junior high schools, contributing significantly to literacy development by fostering students’ critical awareness, motivation, and independent learning culture. Keywords: Literacy, Junior High School, Technology, Microsite, Go Jamu Sumbar.